A Computational Analysis of Two-Phase Casson Nanofluid Passing a Stretching Sheet Using Chemical Reactions and Gyrotactic Microorganisms. (16th June 2019) - Sabir, Zulqurnain; Akhtar, Rizwan; Zhiyu, Zhu; Umar, Muhammad; Imran, Ali; Wahab, Hafiz Abdul; Shoaib, Muhammad; Raja, Muhammad Asif Zahoor
Abstract : In this study, an attempt is made to explore the two-phase Casson nanofluid passing through a stretching sheet along a permeable surface with the effects of chemical reactions and gyrotactic microorganisms. By utilizing the strength of similarity transforms the governing PDEs are transformed into set of ODEs. The resulting equations are handled by using a proficient numerical scheme known as the shooting technique. Authenticity of numerical outcomes is established by comparing the achieved results with the MATLAB built-in solver bvp4c. The numerical outcomes for the reduced Nusselt number and Sherwood number are exhibited in the tabular form, while the variations of some crucial physical parameters on the velocity, temperature, and concentration profiles are demonstrated graphically. It is observed that Local Nusselt number rises with the enhancement in the magnetic field parameter, the porous media parameter, and the chemical reactions, while magnetic field parameter along with porous media parameter retards the velocity profile.